Walter Eucken`s principles of economic policy today - Ulrich van Suntum; Tobias Böhm; Jens Oelgemöller; Cordelius Ilgmann (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2011)
Walter Eucken was the head of the Freiburg school of economics, a circle of German ordoliberal scholars of the interwar period, whose thoughts were highly influential in the immediate post war period. Being disillusioned by what he called the age of experiments- the failure of both classical liberalism and socialism - he formulated eleven principles for what he called a market economy, in which competition would not only limit the extent of private economic power, but also lead to an efficient allocation of resources and hence to economic prosperity. Although the principles never received much international attention, in light of recent economic research on both institutions and welfare economics, the essence of Eucken's work appears to be very modern indeed. This paper highlights these parallels and proposes a reformulation of Eucken's principles against the background of modern economic theory. We thus attempt to make a contribution to the current debate on the efficient design of those institutions that shape economic activity.
Keywords: 330